Uma etnografia sobre memórias e fotografias no terecô: entre possibilidades, interditos e afetos - Freire, Fladney Francisco da Silva (2022)
Although they seem like an individual phenomenon, photographs should also be understood as a collective construction. In this study, besides being important in the plot of memory in the context of Terecô of Bacabal (MA), are pieces that set up a timeline of the Spiritist Tent of Umbanda de São Raimundo Nonato, the terreiro of my family. The thesis seeks to provoke a reflection on the limits and potentialities of the image for religion, portraying how it is used in the temple to narrate the trajectory of the terreiro itself and its members. Throughout the study, we approached the context of Terecô in the municipality of Bacabal(MA ) and the genesis of the terreiro, also trying to understand the conception that religious leaders and scholars have about the importance of image in the production of knowledge, without leaving aside the approach to care for the dissemination of these photographs, since religion is historically the target of prejudices. In the terreiro, it is believed that the care with the way these records reach the spaces outside the walls is able to collaborate with the breaking of stereotypes. Part of this care occurs with the contextualization of the record of rituals that will be exposed – considering that images about Afro-Brazilian religions undergo negative historical construction – and preservation of those that are part of the secret/mystery of Terecô, interdicts that are beyond human decision. It is concluded that the dissemination of images is able to help in the construction of a new look at terecô. In the academic field, the research seeks to guide researchers who use the resource of photography on the best way to act in terreiros that have rules on the dissemination of these images. In addition, another perspective begins here, this time from Bacabal, on terecô, until then portrayed predominantly from the axis of Codó (MA) since most of the published texts deal with terreiros located in this city. In the end, it is understood that photography is capable not only of helping the anthropologist to retrieve information observed in the field and serve as an illustrative element to the reader, but also to provide information that supports the construction of knowledge.